Determinants of utilisation of university of Ibadan agricultural research outputs among farmers in Oyo and Osun states, Nigeria (2021)
The study assessed determinants of farmers’ utilisation of University of Ibadan (UI) Agricultural Research Outputs (AROs) in Oyo and Osun States, Nigeria. A multi-stage sampling procedure was used to select 176 beneficiaries of AROs in the study area. Focus Group Discussion and interview schedule were used for data collection on respondents’ socio-economic characteristics, knowledge, utilisation level and determinants of utilisation of UI AROs. Data was analysed using descriptive and inferential statistics like Chi square, PPMC, and multiple regression. AROs considered for the study were use of neem (Azadirachta indica) extract for pest management, rice-fish-poultry integrated farming system, processing of moringa oleifera powder and ruminant feed block meal pattern. Results reveal that respondents’ mean age household size were 40.05±35.48 years of 4.04±1.25 persons respectively. Respondents had mean farming experience of 7.92±5.26 years. The most utilised source of labour was family (63.0%) with mean farm size of 1.56±0.93 acres. Respondents’ knowledge (67.0%), and utilisation (55.7%) of UI AROs were high for innovations disseminated. Respondents’ marital status (χ2=5.99), sex (χ2=3.92), level of education (χ2=30.69); age (r=0.23) and income (r=0.79) were significantly related to UI AROs utilisation. Respondents’ knowledge (r=0.32) and benefits derived (r=0.80) were significantly related to utilisation of UI AROs. The determinants of utilisation of the AROs included educational qualification (β = 0.462), years of farming or processing experience (β=0.27), scale of production (β=0.33) and knowledge on utilisation (β=0.45). The study recommends that farmers be encouraged to improve on their level of education for better utilisation of disseminated agricultural research outputs.